Acetal Metathesis: Mechanistic Insight - Pemba, Alexander G.; Miller, Stephen A. (Synlett, 2019)
The origins and recent applications of acetal metathesis are discussed in the context of synthesizing polyacetals via acetal metathesis polymerization (AMP). A kinetic study of the acid-catalyzed acetal metathesis reaction suggests the rate = k[H+][acetal]2, with MeOCH2OMe and EtOCH2OEt interchanging to yield MeOCH2OEt, achieving the statistical 1:2:1 equilibrium distribution in 4 hours at 80 °C and in 1 hour at 90 °C. Upon heating 1,10-decanediol and diethoxymethane, polydecylene acetal is formed with sequential distillation of ethanol, followed by diethoxymethane. A full mechanism for this polymerization is proposed, which begins with a transacetalization sequence to convert the diol into a bisacetal, followed by acetal metathesis to yield a high-molecular-weight polymer.
Keywords: acetal; metathesis; transacetalization; polyacetal; acid catalysis; kinetic study; nucleophilicity